DESAIN APLIKASI OBYEK WISATA KOTA PACITAN BERBASIS ANDROID - Susilo, Dahlan; Al Haris, Firdhaus Hari Saputro; Ariwibowo, Heru (JURNAL GAUNG INFORMATIKA, 2015)
The tourism sector is one of the main sectors of economic activity oriented to the expansion of employment and employment opportunities. Pacitan city in general has awide range of tourist attractions that are very potential to increase Pacitan income. In recent time, Pacitan Regency does not yet have an android application that providesinformation related to tourism in the pacitan that can be accessed offline and can access the locations which connected with google maps . The purpose of this research isto build the application of Pacitan tourism based Android with the aim to facilitate the public in general to access information related to pacitan city tour that they need.The Methods used for data collection are literature method, observation, interview, analysis, design, programming, testing and implementation. The Analysis ofdata used object-based with Use Case Diagram, Use Case Realization Diagram Class Diagram, Activity Diagram, Sequence Diagram, Component Diagram, and DeploymentDiagram.